Identification of system damping in railway catenary wire systems from full-scale measurements. (15th April 2016) - Nåvik, Petter; Rønnquist, Anders; Stichel, Sebastian
Highlights: An identification of system damping in railway catenary systems is presented. A wireless sensor system is used to sample accelerations on existing catenary systems. Full-scale measurements are successfully used to identify modal parameters. The system damping of different catenaries is of the same magnitude. Recommended Rayleigh damping coefficients for numerical models are proposed. Abstract: Damping is an important property in predicting the response of any civil or mechanical engineering structure, including railway catenary systems. Numerical models describing the pantograph–catenary interaction are dependent on a proper description of the structural damping for both systems to obtain accurate results. A proper description of the damping in different pantographs can easily be found in the literature. However, few studies have considered the damping properties in railway catenary systems even though such systems are considered to be lightly damped. The aim of this study was to identify the system damping of catenary sections by thoroughly analyse several recorded acceleration time series. These time series were sampled in several points on three different existing railway catenary systems, rendering a good description of the system damping in the frequency range of 0–20 Hz. The covariance-driven stochastic subspace identification (Cov-SSI) method was used to analyse the time series, and Rayleigh coefficients were successfully identified for all three catenary sections.